2018
DOI: 10.1016/j.coche.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell technologies for profiling T cells to enable monitoring of immunotherapies

Abstract: Immunotherapy relies on the reinvigoration of immune system to combat diseases and has transformed the landscape of cancer treatments. Clinical trials using immune checkpoint inhibitors (ICI), and adoptive transfer of genetically modified T cells have demonstrated durable remissions in subsets of cancer patients. A comprehensive understanding of the polyfunctionality of T lymphocytes in ICI or adoptive cell transfer (ACT), at single-cell resolution, will quantify T-cell properties that are essential for therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…The elevated GrB production that was observed in peripheral blood mononuclear cells isolated from patients could provide information about the disease and thus shows the platform's potential utility for diagnosis. Although it is assumed that the elevated GrB levels are due to increased expression by CTL activation; the contribution from other immune cells is lacking in reports 31.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated GrB production that was observed in peripheral blood mononuclear cells isolated from patients could provide information about the disease and thus shows the platform's potential utility for diagnosis. Although it is assumed that the elevated GrB levels are due to increased expression by CTL activation; the contribution from other immune cells is lacking in reports 31.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the protease expression of the immune cells, specific T cell subset responsible for the anti-tumor response can be identified. These cells with overexpression of GrB has been an interest especially in immune checkpoint inhibitors immunotherapy and adaptive cell transfer therapy 31-32.…”
Section: Resultsmentioning
confidence: 99%
“…Many research works have demonstrated its advantages in having fast isolation speed and high efficiency of data acquisition. These platforms are capable of spatial control of liquid composition, cell and cell environment manipulation, and single cell handling and quantification of secreted molecules 3 5 . Thus, microfluidic platforms are an important tool for single cell studies as it allows the identification of rare subsets and resolution between cells with same expression patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, microfluidic platforms are an important tool for single cell studies as it allows the identification of rare subsets and resolution between cells with same expression patterns. This has become an important tool for single cell biological research taking advantage of massive parallel processing, streamlining of complex protocols, and enabling high-throughput biological experiments 3 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Many research works have demonstrated its advantages in having fast isolation speed and high efficiency of data acquisition. It is capable of integrating multiple workflows that enables parallelization and streamlining of complex protocols, which allows automation and control of analytical functions, cell and cell environment manipulation, and simultaneous detection and quantification of secreted molecules 3,4 . For instance, conventional approaches don't take into account the phenotypic and functional state of heterogenous cells which microfluidics technology is able to address.…”
Section: Introductionmentioning
confidence: 99%